2022
DOI: 10.1021/acsnano.2c05592
|View full text |Cite
|
Sign up to set email alerts
|

Porous but Mechanically Robust All-Inorganic Antireflective Coatings Synthesized using Polymers of Intrinsic Microporosity

Abstract: Here, we introduce polymer of intrinsic microporosity 1 (PIM-1) to design single-layer and multilayered all-inorganic antireflective coatings (ARCs) with excellent mechanical properties. Using PIM-1 as a template in sequential infiltration synthesis (SIS), we can fabricate highly uniform, mechanically stable conformal coatings of AlO x with porosities of ∼50% and a refractive index of 1.41 compared to 1.76 for nonporous AlO x that is perfectly suited for substrates commonly used in high-end optical systems o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Prior studies have shown that incorporating a refractive index gradient across the thickness of a film is an efficient method to produce a broadband ARC. ,, To produce such a structure, we infiltrate subsaturating amounts of PMMA into the disordered packings of hollow NPs. To control the extent of UCaRI, we define the volume fraction of PMMA in each film as ϕ PMMA = h PMMA h NP , where h PMMA and h NP are the thicknesses of the PMMA layer and hollow silica NP layer, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that incorporating a refractive index gradient across the thickness of a film is an efficient method to produce a broadband ARC. ,, To produce such a structure, we infiltrate subsaturating amounts of PMMA into the disordered packings of hollow NPs. To control the extent of UCaRI, we define the volume fraction of PMMA in each film as ϕ PMMA = h PMMA h NP , where h PMMA and h NP are the thicknesses of the PMMA layer and hollow silica NP layer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies have shown that the mechanical fragility of NP films can be mitigated through techniques like high-temperature sintering, atomic layer deposition, and hydrothermal treatment, controlling their structures remains challenging. ,, For instance, in the fabrication and utilization of ARCs for optical devices, graded porous structures are highly advantageous in suppressing reflection across a wide range of the visible light spectrum. However, most studies have generated gradients in films by sequentially coating multiple different materials onto substrates, which is complex and time-consuming. ,, Such multilayered coatings and films are not continuous due to the presence of interfaces between each layer, which could potentially degrade their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the development of antireflective, self-cleaning, antifreeze and other types of coatings on silicate glass. Glass with antireflective coatings are in high demand for solar panels, LED modules, greenhouses and other applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a positive peak referring to a reflectance increase was observed at low concentrations, and a negative response referring to a reflectance increase was found at high concentrations of xylene. The replacement of carrier gas molecules (nitrogen) in the cavity with xylene increased the average refractive index of SURMOFs, which created an antireflective effect leading to a positive response of xylene sensing. , The extra adsorption capacity generated more localized and effective scattering and led to a negative response, which was induced by the increase of the refractive index contrast between the frame and the cavity of the MOFs. , Analyzing the appearance of the first negative peak, the resonator with arrays of P = 20 μm had a response time ( t 1 – t 0 ) of 20.2 s at the xylene concentration of 120 ppm. Similarly, the resonators with arrays of P = 40 showed a fast response time of 5.2 s at 30 ppm, and the resonators with arrays of P = 60 μm showed a response time of 6.5 s at 90 ppm.…”
mentioning
confidence: 99%
“…The replacement of carrier gas molecules (nitrogen) in the cavity with xylene increased the average refractive index of SURMOFs, which created an antireflective effect leading to a positive response of xylene sensing. 40,41 The extra adsorption capacity generated more localized and effective scattering and led to a negative response, which was induced by the increase of the refractive index contrast between the frame and the cavity of the MOFs. 42,43 Analyzing the appearance of the first negative peak, the resonator with arrays of P = 20 μm had a response time (t 1 − t 0 ) of 20.2 s at the xylene concentration of 120 ppm.…”
mentioning
confidence: 99%